CRISPR-Cas9: From a bacterial immune system to genome-edited human cells in clinical trials. Issue 3 (4th May 2017) - Kick, Leonhard; Kirchner, Marion; Schneider, Sabine
ABSTRACT: The adaptive bacterial immune system CRISPR-Cas is revolutionizing all fields of life science and has opened up new frontiers toward personalised medicine. Since the elucidation of the molecular mechanism of Cas9 from Streptococcus pyogenes in 2012 and its development as a genomic engineering tool, genetic modifications in more than 40 species have been performed, over 290 patents have been filed worldwide and the first clinical trials using CRISPR-Cas-modified T-cells have recently been started in China and in the US. In this review we summarise current design developments, novel Cas systems and their antagonists, present and potential future applications as well as the ongoing debate on ethical issues, which has arisen through the CRISPR-Cas technology.